Creep compliance of functionalized graphene-epoxy nanocomposites - Bakbak, Okan; Colak, Ozgen (GOLDEN LIGHT PUBL, 2024)
Creep behavior is observed even at room temperature in polymers and polymer composites under constant stress. In the design of structural elements using these materials, the determination of creep compliance for structural strength and performance analysis is crucial in terms of reliability and usability. In this study, the creep compliance of pure epoxy and functionalized graphene-reinforced epoxy nanocomposites were experimentally investigated and compared at room temperature at constant stress levels of 50, 100, and 200 MPa representing the viscoelastic region, yielding region and viscoplastic region, respectively. To reveal the effect of temperature as well as stress level on this behavior, the creep compliance of epoxy and graphene-epoxy nanocomposites was investigated at 65 degrees C in addition to room temperature after the pure graphene used as a reinforcement element was functionalized with Triton X-100, nanocomposite production was carried out. In 2h creep tests, it was observed that as the constant stress level increased, the creep compliance increased and the creep compliance of the nanocomposite was lower than that of the epoxy at all stress levels. The creep compliance of the epoxy was improved by 65% with the addition of functionalized graphene at room temperature and a stress level of 100 MPa. As the temperature increased, the creep compliance of both epoxy and functionalized graphene-epoxy nanocomposite increased due to molecular mobility and viscous flow. However, at high temperatures, the positive effect of functionalized graphene on the compliance of the epoxy is higher. At 65 degrees C and a stress level of 100 MPa, the improvement rate of creep compliance is 78%. Functionalized graphene exhibited a more effective behavior on creep resistance at high temperatures. The obtained results showed that creep compliance was significantly affected by stress level and temperature.
Keywords: Viscoelasticity; Epoxy; Functionalized graphene; Nanocomposite; Creep compliance; MECHANICAL-PROPERTIES; CARBON; COMPOSITES; BEHAVIOR; SIZE; Construction & Building Technology; Engineering